Risk factors of multidrug-resistant, extensively drug-resistant and pandrug-resistant Acinetobacter baumannii ventilator-associated pneumonia in a Medical Intensive Care Unit of University Hospital in Thailand - Inchai J. (Springer Japan, 2015)
© 2015 Japanese Society of Chemotherapy and The Japanese Association for Infectious Diseases. Ventilator-associated pneumonia (VAP) caused by Acinetobacter baumannii remains a significant cause of morbidity and mortality. Increasing antimicrobial resistance influences the selection of antibiotic treatment especially pandrug-resistant A.baumannii. A retrospective cohort study was conducted in the Medical Intensive Care Unit to identify the risk factors of VAP caused by multidrug-resistant A.baumannii (MDR-AB), extensively drug-resistant A.baumannii (XDR-AB) and pandrug-resistant A.baumannii (PDR-AB). All 337 adult patients with confirmed A.baumannii VAP were included. The incidence of MDR-AB, XDR-AB and PDR-AB were 72 (21.4%), 220 (65.3%) and 12 (3.6%), respectively. The risk factor for MDR-AB was prior use of carbapenems (OR 5.20; 95% CI 1.41-19.17). Risk factors for XDR-AB were the prior use of carbapenems (OR, 6.30; 95% CI, 1.80-21.97) and a high Sequential Organ Failure Assessment (SOFA) score (OR 1.35; 95% CI 1.07-1.71). In PDR-AB, the risk factors were the prior use of colistin (OR, 155.95; 95% CI, 8.00-3041.98), carbapenems (OR, 12.84; 95% CI, 1.60-103.20) and a high Simplified Acute Physiology Score (SAPS II) (OR 1.10; 95% CI 1.01-1.22). In conclusion, previous exposure to antibiotics and severity of VAP were risk factors of drug-resistant A. baumannii. Judicious use of carbapenems and colistin is recommended to prevent the antimicrobial-resistant strains of this organism.